Linear Optical, Quadratic and Cubic Nonlinear Optical, Electrochemical, and Theoretical Studies of "Rigid‐Rod" Bis‐Alkynyl Ruthenium Complexes2. Issue 7 (18th April 2018) - Babgi, Bandar A.; Kodikara, Mahesh S.; Morshedi, Mahbod; Wang, Huan; Quintana, Cristóbal; Schwich, Torsten; Moxey, Graeme J.; Van Steerteghem, Nick; Clays, Koen; Stranger, Robert; Cifuentes, Marie P.; Humphrey, Mark G.
Abstract: The syntheses of oligo( p‐ phenylene ethynylene)s (OPEs) end‐functionalized by a nitro acceptor group and with a ligated ruthenium unit at varying locations in the OPE chain, namely, trans ‐[Ru{(C≡C‐1, 4‐C6 H4 ) n NO2 }(C≡CR)(dppe)2 ] (dppe=1, 2‐bis(diphenylphosphino)ethane; n =1, R=1, 4‐C6 H4 C≡C‐1, 4‐C6 H4 C≡CPh, 1, 4‐C6 H4 NEt2 ; n =2, R=Ph, 1, 4‐C6 H4 C≡CPh, 1, 4‐C6 H4 C≡C‐1, 4‐C6 H4 C≡CPh, 1, 4‐C6 H4 NO2, 1, 4‐C6 H4 NEt2 ; n =3, R=Ph, 1, 4‐C6 H4 C≡CPh), are reported. Their electrochemical properties were assessed by cyclic voltammetry, their linear optical properties and quadratic and cubic nonlinear optical properties were assayed by UV/Vis/NIR spectroscopy, hyper‐Rayleigh scattering studies employing nanosecond pulses at 1064 nm, and broad spectral range Z‐scan studies employing femtosecond pulses, respectively, and their linear optical properties and vibrational spectroscopic behavior in the formally Ru III state was examined by UV/Vis/NIR and IR spectroelectrochemistry, respectively. The potentials of the metal‐localized oxidation processes are sensitive to alkynyl‐ligand modification, but this effect is attenuated on π‐bridge lengthening. Computational studies employing time‐dependent density functional theory were undertaken on model complexes, with a 2D scan revealing a soft potential‐energy surface for intra‐alkynyl‐ligand aryl‐ring rotation; this is consistent with the experimentally observed blueshift in optical absorption maxima. Quadratic optical nonlinearities are significant and cubic NLO coefficients for these small complexes are small. The optimum length of the alkynyl ligands and the ideal metal location in the OPE to maximize the key coefficients have been defined. Abstract : Hot rods ! The quadratic and cubic optical nonlinearities of oligo( p‐ phenylene ethynylene)s ( n OPEs)—end‐functionalized by a nitro acceptor group and with a ligated ruthenium unit at varying locations in the n OPE chain—increase on proceeding from 1PE to 2PE, but decrease on further chain lengthening, thereby defining the optimum bridge length for nonlinear optical effects in such complexes (see figure).